Conditional deletion of Eps8 reduces hippocampal synaptic plasticity and impairs cognitive function. (January 2017) - Wang, Yu-Ting; Huang, Chiung-Chun; Lin, Yun-Shan; Huang, Weu-Fang; Yang, Cheng-Yi; Lee, Cheng-Che; Yeh, Che-Ming; Hsu, Kuei-Sen
Abstract: Epidermal growth factor receptor substrate 8 (Eps8) is a multifunctional protein involved in actin cytoskeleton regulation and is abundantly expressed in many brain regions. However, the functional significance of Eps8 in the brain has only just begun to be elucidated. Here, we demonstrate that genetic deletion of Eps8 (Eps8 −/− ) from excitatory neurons leads to impaired performance in a novel object recognition test. Consistently, Eps8 −/− mice displayed a deficit in the maintenance of long-term potentiation in the CA1 region of hippocampal slices, which was rescued by bath application of N -methyl-d -aspartate receptor (NMDAR) antagonist 2-amino-5-phosphonopentanoate. While Eps8 −/− mice showed normal basal synaptic transmission, a significant increase in the amplitude and a significantly slower decay kinetic of NMDAR-mediated excitatory postsynaptic currents (EPSCs) were observed in hippocampal CA1 neurons. Furthermore, a significant increase in the expression of ifenprodil-sensitive NMDAR-mediated EPSCs was observed in neurons from Eps8 −/− mice compared with those from wild-type mice. Eps8 deletion led to decreased mature mushroom-shaped dendritic spine density but increased complexity of basal dendritic trees of hippocampal CA1 pyramidal neurons. These results implicate NMDAR hyperfunction in the cognitive deficits observed in Eps8 −/− mice and demonstrate a novel role for Eps8 in regulating hippocampal long-term synaptic plasticity and cognitive function. This article is part of the Special Issue entitled 'Ionotropic glutamate receptors'. Highlights: Eps8 deletion results in NMDA receptor hyperfunction. Eps8 deletion promotes decay of long-term potentiation. Eps8 deletion leads to cognitive deficits.